ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA DALAM PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) (STUDI KASUS PADA KELOMPOK TANI TAMAN KEHATI BINAAN PT AQUA GOLDEN MISSISSIPI) - Novindra .; Ghina Salsabila (Journal of Integrated Agribusiness, 2023)
Companies as national economic development actors must contribute to improving the welfare of the surrounding environment, this form of concern is through the Corporate Social Responsibility (CSR) program of companies that have implemented CSR programs, namely PT. Aqua Golden Mississippi is located in Babakan Pari Village, Cidahu District, Sukabumi Regency. Large companies can of course optimize their social assistance to be able to help improve the economy of the community around the company. The aims of this study were (1) to describe the implementation of PT AGM's CSR in Taman Kehati farmer groups, and (2) to analyze household income before and after receiving the PT. ECODEV CSR program. AGM, (3) analyzing the welfare of households receiving the ECODEV PT CSR program. AGM. The research was carried out in the assisted villages as the place for the ECODEV program to be implemented. The method used is an analysis of household income and expenditure using the approach of Sajogyo (1997), the World Bank, and BPS. The results of the study showed that the Taman Kehati farmer group was a group fostered by PT. AGM which is engaged in agriculture, the income of farmer households has increased after participating in the ECODEV CSR program which comes from the main business income. The farmer's expenditure value is above the welfare criteria, therefore, the majority of the Taman Kehati Group farmer households belong to the category of non-poor households.